APPLICATION OF SOFTWARE PLATFORMS TO ENHANCE EARLY WARNING AND DETECTION SYSTEM CAPABILITIES FOR NUCLEAR WEAPONS THREAT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The report describes the potential damage from the striking factors of low- and medium-yield nuclear munitions. A scenario of a terrestrial nuclear explosion in a city is modelled. Analytical calculations are proposed for nuclear blast damage for which no simulation platform is implemented. An analysis was made of the damage to residential buildings and the population from the light pulse, radiation pollution through a software platform. Data for the electromagnetic pulse area are extracted. A comparison was made of the sizes of the damage zones for the striking factors of the nuclear weapon in the respective powers of the nuclear explosion.